2010
DOI: 10.3989/ajbm.2251
|View full text |Cite
|
Sign up to set email alerts
|

Comparación de la flora exótica vascular en sistemas de islas continentales: Cerdeña (Italia) y Baleares (España)

Abstract: This paper provides a comparison of the vascular exotic flora of Sardinia and that of the Balearic Islands, both territories belonging to the Western Mediterranean biogeographic subregion. The study has recorded 531 exotic taxa in Sardinia (18.8% of the total flora) while 360 (19%) in the Balearic Islands; 10 are new to Sardinia (3 of which for Italy) and 29 to the Balearic Islands. The alien flora of Sardinia is included in 99 families; Fabaceae is the richest (49 taxa), followed by Poaceae (33) and Asteracea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
18
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 47 publications
5
18
0
3
Order By: Relevance
“…These data are consistent with those observed in other contexts of the Mediterranean islands, e.g., the Balearic Islands (19%, Podda et al, 2010), and are significantly higher than those reported for Sicily (12.55%, Raimondo et al, 2010) and for the Tuscan Archipelago (10%, Lazzaro et al, 2014).…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…These data are consistent with those observed in other contexts of the Mediterranean islands, e.g., the Balearic Islands (19%, Podda et al, 2010), and are significantly higher than those reported for Sicily (12.55%, Raimondo et al, 2010) and for the Tuscan Archipelago (10%, Lazzaro et al, 2014).…”
Section: Discussionsupporting
confidence: 81%
“…The American predominance featuring alien flora -invasive and not invasive-of Sardinia and Corsica, is a constant in many Mediterranean areas, both islands -such as the Balearic Islands (Podda et al, 2011(Podda et al, , 2010 (Arianoutsou et al, 2010). Other relatively important contributions to the exotic flora of Sardinia and Corsica, as for the other mentioned territories, come from Asia, from the Mediterranean basin and the African continent; with respect to the invasive flora, it is to be noted that the Mediterranean component is significantly reduced.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations